Article review: Research on the impact of communications technology on student communication skill / Nurfatihah Abdul Razak and Norhashidah Kifli - Abdul Razak, Nurfatihah; Kifli, Norhashidah (Faculty of Information Management, 2015)
The use of computer communications technology has been growing rapidly in the environment, that were included children, teenagers and others. Presently, computer-facilitated communications technology like chat services, email and Skype face-to-face chat services are everyday part of the life of student. However, what is uncertain is what effect this ahs on the student's abilities to communicate. It could improve communication skills, or prevent students to realize the needed of communication skills. This research is designed to identify the effect or computer-based in communication aspect that demonstrated by students.